Global multidimensional poverty index 2019 : illuminating inequalities - United Nations Development Programme Human Development Report Office; Oxford Poverty And Human Development Initiative (Oxford Poverty and Human Development Initiative (OPHI), 2019)
The 2019 global MPI publication Illuminating Inequalities released on 11 July 2019 sheds light on the number of people experiencing poverty at regional, national and subnational levels, revealing inequalities across countries and among the poor themselves. The publication is jointly developed by the Oxford Poverty and Human Development Initiative (OPHI) at the University of Oxford and the United Nations Development Programme Human Development Report Office (UNDP HDRO). The global MPI provides a comprehensive and in-depth picture of global poverty – in all its dimensions – and monitors progress towards Sustainable Development Goal (SDG) 1 – to end poverty in all its forms. The publication previews ongoing research into trends over time for a group of countries including Bangladesh, Democratic Republic of Congo, Ethiopia, Haiti, India, Nigeria, Pakistan, and Peru. SDG target 10.1 calls for tracking the progress of the bottom 40 percent of the population compared with that of the total population – the publication includes case studies and a detailed analysis of the growth of those furthest behind – the ‘bottom 40%’.